A cross-cultural comparison of mathematics teachers’ noticing on task potential and its use in developing flexible problem-solving strategies - Lin, Yu-Ting; Paul, Josephine; Lindmeier, Anke; Dreher, Anika; Hsieh, Feng-Jui; Wang, Ting-Ying (Proceedings of the 47th Annual Conference of the International Group for the Psychology of Mathematics Education, 2024)
CRIS-Team Scopus Importer:2024-10-02

Are experts’ noticing focuses regarding the learning potential of tasks and its use consistent across instructional situations? A secondary analysis - Paul, Josephine F.; Dreher, Anika; Wang, Ting-Ying; Hsieh, Feng-Jui; Hansen, Linn; Lindmeier, Anke (Proceedings of the 46th Conference of the International Group for the Psychology of Mathematics Education, 2023)
Professional noticing is an important aspect of teacher expertise. Research has shown that noticing might vary between cultures. Prior studies indicate that culture-specific norms influence noticing. But, these findings stem from group comparisons. The reported study aims at understanding how individual focuses may influence noticing in addition to cultural influences. It uses noticing vignettes to investigate the aspects Western (German, N=17) and East Asian (Taiwanese, N=19) professors in mathematics education (experts) focus their attention on when evaluating the potential of tasks for mathematical learning and its use in instruction. We present preliminary results regarding the consistency of the focuses across situations, identify five types of experts regarding their focuses, and discuss implications for further noticing research.
CRIS-Team Scopus Importer:2024-10-02

Culture-Specific Norms Regarding High-Quality Use of Task Potential for Mathematical Learning—Contrasting Researchers’ Perspectives from Germany and Taiwan - Paul, Josephine F.; Dreher, Anika; Wang, Ting-Ying; Hsieh, Feng-Jui; Lindmeier, Anke (Journal für Mathematik-Didaktik, 2024)
Factors like the potential of tasks to support students’ mathematical learning and its use in instruction are consensually understood to be relevant for instructional quality across cultural contexts. Yet, research has also shown that perspectives on instructional quality may vary between cultural contexts. As an explanation, it is argued that such perspectives depend on instructional norms, which correspond to the expected behavior in instruction within a cultural context. Notably, research contrasting mathematics instruction from East Asian and Western cultures hints at potentially different instructional norms regarding high-quality use of task potential, but systematic evidence is lacking so far. This study addresses this gap and uses three text vignettes of instructional situations to systematically elicit and contrast instructional norms regarding the use of word problems for mathematical learning. Researchers from Germany (N = 17) and Taiwan (N = 19) evaluated the use of tasks in various instructional situations in an online survey, and their answers were qualitatively analyzed to determine possible culture-specific norms based on their reasoning. In two of the three cases, culture-specific norms in line with assumptions could be identified. In the third case, researchers in both countries referred to an interculturally shared instructional norm. Differences between the reasoning in answers from Germany and Taiwan indicate further cultural influences in line with assumptions based on prior research. We discuss the findings and their implications for the validity of intercultural research in mathematics education.
CRIS-Team Scopus Importer:2024-10-02
Keywords: Cross-cultural research; Cultural norms; Instructional norms; Intercultural validity; Quality of mathematics instruction

Exploring mathematics teachers’ noticing on responding to student thinking — a crosscultural comparison between Taiwan and Germany - Yeh, Fung-Wen; Paul, Josephine; Dreher, Anika; Lindmeier, Anke; Hsieh, Feng-Jui; Wang, Ting-Ying (Proceedings of the 47th Annual Conference of the International Group for the Psychology of Mathematics Education, 2024)
CRIS-Team Scopus Importer:2024-10-02

Fruit salad algebra – a comparison of experts’ and mathematics teachers’ noticing - Larrain, Macarena; Paul, Josephine; Lindmeier, Anke; Hsieh, Feng-Jui; Wang, Ting-Ying; Dreher, Anika (Proceedings of the 45th Conference of the International Group for the Psychology of Mathematics Education, 2022)
CRIS-Team Scopus Importer:2024-10-02

Kategorisierung von Fachbegriffen zum Mathematikunterricht im Bereich quadratische Gleichungen und Funktionen - Paul, Josephine; Leiß, Dominik; Lindmeier, Anke (Beiträge zum Mathematikunterricht 2022, 2023)

Posen, Hypen, Inszenieren. Zur digitalen Bedeutungsaufladung von Socially Hyped Locations - Paul, Josephine Friederike (Wochenschau Verlag, 2023)

The role of experts' norms of instructional quality for assessing teacher noticing. Revealing culture-specific and interculturally shared norms of mathematics education in Germany and Taiwan - Lindmeier, Anke; Paul, Josephine Friederike; Wang, Ting-Ying; Hsieh, Feng-Jui; Dreher, Anika (Teacher Professional Vision: Empirical Perspectives, 2025)

Weshalb richtet sich das Noticing bei der Beurteilung des Einsatzes von Aufgaben auf die Schüler:innenaktivität? – Untersuchung individueller, kultureller und situativer Einflüsse - Paul, Josephine Friederike; Dreher, Anika; Lindmeier, Anke (Beiträge zum Mathematikunterricht, 2024)